MITIGASI BENCANA PERUBAHAN IKLIM DALAM PENGEMBANGAN DESA WISATA HIJAU DESA GONDANG KECAMATAN LIMBANGAN - Jamilla Kautsary; Ardiana Yuli Puspitasari; Abdul Rochim; Adelia Salsabila Anugrah; Feldian Hendargi (Pondasi, 2022)
Gondang Village is a tourist village in the upper part of Kendal district with high morphological characteristics (tends to be hilly). Gondang village is currently developing as a tourist village, only tourism that is developing leads to mass tourism which is oriented towards bringing in large numbers of tourists. This condition is certainly very contrary to efforts to develop tourist villages which place more emphasis on conservation aspects. The consequence is an increase in disaster risk, both in the form of increased run off during the rainy season (increased flood discharge) and drought during the dry season in shaded areas, as well as increased ground movement. This community service aims to find solutions so that tourism village development efforts can still run, but can reduce disaster risk by disaster mitigation. The disaster mitigation in question is by regulating land use based on multiple disasters and improving the structural design of tourism supporting facilities and infrastructure.